The relation between nonalcoholic fatty liver disease and carotid intima-media thickness in Egyptian patients. Issue 1 (January 2017) - Riad, George S.; Kaisar, Hany H.; Hussein, Hany A.; Hussein, Ahmed
Abstract : Background and aim: Nonalcoholic fatty liver disease (NAFLD) is strongly associated with obesity, type II diabetes, and dyslipidemia. Thus, NAFLD shares many features of the metabolic syndrome, a highly atherogenic condition, and its presence could signify a substantial cardiovascular risk. The intima-media thickness (IMT) of the carotid artery is a reliable indicator of subclinical atherosclerosis, and it has been shown that increased IMT is associated with increased prevalence and incidence of myocardial infarction and stroke. In recent years, carotid artery IMT measurements by high-resolution carotid B-mode ultrasonography have been widely used to study the severity and progression of atherosclerosis. This study was designed to assess the correlation between NAFLD as a cardiovascular risk factor and carotid atherosclerosis. Patients and methods: A hospital-based case–control analytical study was conducted on 60 participants who were divided into three groups as follows. Group I included 20 diabetic patients with NAFLD. Group II included 20 nondiabetic patients with NAFLD. Group III included 20 healthy participants who served as a control group. The right and left carotid intima-media thickness (CIMTs) and their maximum reading (CIMTmax) was measured by a skilled sonographer blind to the groups. Pelviabdominal ultrasound was performed for all participants, and the sonographic grading of the NAFLD was determined in groups I and II. Histological grading of hepatic steatosis was done by liver biopsy in groups I and II. Results: In comparison with the control group, the median CIMTmax was significantly higher in group I and group II ( P <0.001), but there was no statistically significant difference between groups I and II ( P <0.792). There was a statistically significant positive correlation between CIMT and severity of NAFLD ( P <0.001). Strong association is found between the increase of liver enzymes level and increase of carotid IMT in patients of NAFLD, which was highly significant ( P <0.001). Conclusion: There is a significant association between the presence of NAFLD and atherosclerosis; this association was independent of diabetes mellitus presence. The grade of NAFLD and elevated liver enzymes have a significant effect on severity of atherosclerosis.